How Motorcyclists Will Respond to Congestion Charging in Jakarta, Indonesia - Yugihartiman, Masrono; Herawati, Herawati (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
Congestion charging is planned to be implemented in Jakarta, Indonesia to replace the current odd-even traffic policy. Even though motorcycles account for the largest component of traffic in Jakarta, at around 75.8%, few studies exist on the effects of policy changes on motorcycle commuter trips. At the moment, motorcyclists are explicitly excluded from the odd-even scheme, therefore research on their response to congestion charging is worth doing. The response of travelers to such a policy may include transport mode shifting, route diversion, or choosing not to travel. Most studies on the influence of congestion charging emphasize one possible response, namely modal shifting. In this study, the responses studied included modal shifting, route diversion, and the possibility of telecommuting. A total of 421 out 2,125 people who answered the e-survey questionnaire were chosen as the sample. They were evenly distributed across all areas of Greater Jakarta, through which eight corridors pass. The model was analyzed using the multinomial logit model and the conditional logit model to estimate the attribute parameters of each alternative and the probability of choices, employing the NLOGIT6 econometric software. The results of the study were compared to other recent studies, providing consistent results. In-vehicle time, congestion charging rate, and public transportation fare were found to be significant factors, at α = 0.05. The socio-demographic variables income and motorcycle ownership and the travel characteristic weekly trip frequency significantly influenced the travel behavior of motorcyclists. As for the probability that motorcyclists are willing to pay a congestion charge it was found that about one-third of all motorcycle travelers say they are willing to do so, while the probability of motorcyclists diverting to alternative roads accounted for 35.46%, shifting to public transport 16.66%, and deciding not to travel 3.16%.